A hydrostatic test study on the waterproofing of an underground ecological granary using a plastic-concrete system. (October 2022) - Zhang, Hao; Pan, Chongchong; Yang, Jinping; Xi, Han
Abstract: Underground granaries can store grains at low and quasi-low temperatures due to the existing shallow geothermal energy, which can ensure long-term quality and grain preservation. However, water and moisture resistance of groundwater is a key technical problem which restricts its wide application. Consequently, a polypropylene plastic-concrete wall was proposed in this study to solve these problems. First, a hydraulic test was performed on three plastic-concrete specimens using polypropylene plastic (PP) plates of different thicknesses including 10, 15, and 20 mm to investigate the mechanical performance under water pressure loading. The displacement, deformation, interior force, failure mode, and mechanism of the plastic-concrete specimens were comprehensively analysed. Second, a lining waterproof component model was established based on the ABAQUS software. Finally, the interior force adjustment coefficient calculation formulas and interior force analysis method are presented according to the experimental results and direct design method for column-supported slabs. Consequently, the ultimate bearing capacities of the specimens with different PP plate thicknesses were 120, 180, and 170 kPa, respectively, and the failure modes of the specimens varied with the thickness of the PP plate. Moreover, for thicknesses greater than 15 mm, the ultimate bearing capacity of the specimen was mainly dependent on the strength of the nodes. The numerical simulation results correlated with the experimental data, where the stress and displacement of the plastic waterproof components increased gradually with increasing water pressure. The experimental and simulation results of this study can provide a reference for the waterproof design of underground granaries and widen their practical applications.